Ethylene Insensitive 3-Like 2 is a Brassicaceae-specific transcriptional regulator involved in fine-tuning ethylene responses in Arabidopsis thaliana. (8th May 2022) - Houben, Maarten; Vaughan-Hirsch, John; Mou, Wangshu; Van de Poel, Bram
Abstract : EIL2 is an ethylene-dependent transcription factor that evolved exclusively in the mustard family and operates downstream from EIN3/EIL1. EIL2 is involved in fine-tuning hypocotyl elongation, lateral root formation, and flowering time in Arabidopsis thaliana . Abstract: Ethylene signaling directs a pleiotropy of developmental processes in plants. In Arabidopsis, ethylene signaling converges at the master transcription factor Ethylene Insensitive 3 (EIN3), which has five homologs, EIN3-like 1–5 (EIL1–EIL5). EIL1 is most fully characterized and operates similarly to EIN3, while EIL3–5 are not involved in ethylene signaling. EIL2 remains less investigated. Our phylogenetic analysis revealed that EIL2 homologs have only been retrieved in the Brassicaceae family, suggesting that EIL2 diverged to have specific functions in the mustard family. By characterizing eil2 mutants, we found that EIL2 is involved in regulating ethylene-specific developmental processes in Arabidopsis thaliana, albeit in a more subtle way compared with EIN3/EIL1. EIL2 steers ethylene-triggered hypocotyl elongation in light-grown seedlings and is involved in lateral root formation. Furthermore, EIL2 takes part in regulating flowering time as eil2 mutants flower on average 1 d earlier and have fewer leaves. A pEIL2:EIL2:GFP translational reporter line revealed that EIL2 protein abundance is restricted to the stele of young developing roots. EIL2 expression, and not EIL2 protein stability, is regulated by ethylene in an EIN3/EIL1-dependent way. Despite EIL2 taking part in several developmental processes, the precise upstream and downstream regulation of this ethylene- and Brassicaceae -specific transcription factor remains to be elucidated.